Improving the Quality of Learning Content for Teachers of SMK Windusari Magelang - Purwono Hendradi; Uky Yudatama; Nuryanto; Endah Ratna Arumi; Setiya Nugroho (Universitas Ahmad Dahlan, 2022)
Background: The need to increase the mastery of Information and Computer Technology (ICT) in teaching and learning activities is essential and urgent, especially during the COVID-19 pandemic. The PowerPoint application is a popular application for creating learning content, but most teachers are only at the level of